Factors shaping situated willingness to communicate: A multidimensional perspective in the Indonesian EFL context - Suci Nugrah Amalia; Utami Widiati; Sri Rachmajanti; Mirjam Anugerahwati; Budi Waluyo (Universitas Syiah Kuala, 2024)
The willingness to communicate (WTC) of English-as-a-foreign-language (EFL) students requires a complicated process, including motivational, contextual, metacognitive, and communicative factors. Neglecting the intricate interplay of these factors may impede the attainment of desired levels of student WTC, thus underscoring the need for comprehensive investigation. The purpose of this exploratory factor analysis (EFA) is to investigate the complex interplay of motivational, contextual, metacognitive, and communicative factors as predictors of situated WTC in the Indonesian EFL context, which includes variables such as motivation, learner agency, growth language mindset, classroom environment, metacognition, communication confidence, and L2 self-perceived communicative competence (SPCC). We used Partial Least Squares-Structural Equation Modeling (PLS-SEM) model analysis in a quantitative study design. An online questionnaire with 50 items adapted from prior studies was distributed to 310 EFL students from multiple universities in Indonesia who had taken English classes. The data revealed that motivation, learner agency, growth language mindset, classroom environment, metacognition, communication confidence, and SPCC are major determinants of students WTC. These findings suggest that EFL educators can create language learning programs that encourage active involvement in communication tasks and enhance students WTC by recognizing and utilizing the factors that support it. This could lead to more effective and engaging language learning experiences, resulting in increased WTC in the target language. Further discussion focuses on educational consequences and future research recommendations.